A comparative study of infrared and microwave heating for microbial decontamination of paprika powder - Eliasson, Lovisa; Isaksson, Sven; Lövenklev, Maria; Ahrné, Lilia (Frontiers in Microbiology, 2015)
There is currently a need in developing new decontamination technologies for spices due to limitations of existing technologies, mainly regarding their effects on spices’ sensory quality. In the search of new decontamination solutions, it is of interest to compare different technologies, to provide the industry with knowledge for taking decisions concerning appropriate decontamination technologies for spices. The present study compares infrared and microwave decontamination of naturally contaminated paprika powder after adjustment of water activity to 0.88. Infrared respectively microwave heating was applied to quickly heat up paprika powder to 98°C, after which the paprika sample was transferred to a conventional oven set at 98°C to keep the temperature constant during a holding time up to 20 min. In the present experimental set-up microwave treatment at 98°C for 20 min resulted in a reduction of 4.8 log units of the total number of mesophilic bacteria, while the infrared treatment showed a 1 log unit lower reduction for the corresponding temperature and treatment time. Microwave and infrared heating created different temperature profiles and moisture distribution within the paprika sample during the heating up part of the process, which is likely to have influenced the decontamination efficiency. The results of this study are used to discuss the difficulties in comparing two thermal technologies on equal conditions due to differences in their heating mechanisms.